The medium can influence the message: Print‐based versus digital reading influences how people process different types of written information. (12th July 2019) - Haddock, Geoffrey; Foad, Colin; Saul, Victoria; Brown, Will; Thompson, Rose
Abstract : While electronic reading devices are extremely popular, research is equivocal regarding their benefits for outcomes such as reader comprehension. Integrating literatures on reading medium comparisons and matching effects in persuasion, this research tested whether comprehension is maximized when the content of the material (e.g., whether it is traditional vs. modern) matches the medium (e.g., reading from a traditional book vs. digital e‐reader). In Study 1, participants read a traditional‐ or modern‐themed short story from either a book or an e‐reader. Story comprehension was greater when participants read from the printed medium compared to the e‐reader, an effect that was marginally moderated by story content, consistent with a matching effect. In Study 2, participants read a persuasive message that emphasized either a traditional versus modern solution to improving health in either a magazine format or on an iPad. Message comprehension was marginally greater among participants who read their message in a printed format. Participants' interest in weight loss showed evidence of a matching effect – participants were more interested in losing weight when a modern solution to obesity article was presented on an iPad compared to a printed format. The results are applied to the study of reading and attitude change.